Fabrication of Polypyrrole-Mcm41 Nanocomposites Using Electrodeposition Method - Yahaya, Rozita (2006)
Purely siliceous MCM-4 1 (SiMCM-4 1) and aluminium-containing MCM-4 1 (AIMCM-41) with different ratios of AVSi were synthesized following a modified procedure of Ryoo and Kim (1 995). PolypyrroleJMCM-4 1 (PPyJMCM-4 1) conductive polymer nanocomposite films was electrochemically prepared on Indium Tin Oxide (ITO) glass electrode from an aqueous solution of pyrrole monomer and ptoluene sulfonate dopant in a suspension of prepared MCM-41. Various PPy/MCM- 41 nanocomposite films were obtained by varying the experimental conditions with the objective of producing conductive polymer nanocomposites with enhanced thermal and conductivity properties. The prepared nanocomposite films were characterized by Fourier Transform Infrared (FTIR) Spectroscopy, X-ray diffraction (XRD) analysis, Thermogravimetric Analysis, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and conductivity measurements. From observations of the XRD patterns, nanocomposites prepared at low AVSi ratio (PPyJA130 and PPyJA140) and PPyJSiMCM-41 showed better crystallinity compared to those prepared at high AlJSi ratio (PPyJA160 and PPyJA180) which was observed to be amorphous. FTIR and XRD studies showed that the PPy and SiMCM-41 are the most compatible for the formation of PPyJSiMCM-41 nanocomposite. The TGA analysis and conductivity studies showed that the best nanocomposite was PPyJSiMCM-41 which was found to be the most thermally stable with the highest conductivity of 5.24 SJcm. This sample was obtained with optimum condition with 0.5 M pyrrole, 0.1 M p-toluene sulfonate and 3 g/dm3 MCM-41 at 1.2 volt (vs SCE).